2017
DOI: 10.5194/tc-11-1465-2017
|View full text |Cite
|
Sign up to set email alerts
|

Numerical homogenization of the viscoplastic behavior of snow based on X-ray tomography images

Abstract: Abstract. While the homogenization of snow elastic properties has been widely reported in the literature, homogeneous rate-dependent behavior responsible for the densification of the snowpack has hardly ever been upscaled from snow microstructure. We therefore adapt homogenization techniques developed within the framework of elasticity to the study of snow viscoplastic behavior. Based on the definition of kinematically uniform boundary conditions, homogenization problems are applied to 3-D images obtained from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…Up to now, many studies have focused on retrieving the single-scattering properties of individual ice crystals with "idealized" shapes (e.g. Xie et al, 2006;Picard et al, 2009;Liou et al, 2011;Räisänen et al, 2015;Dang et al, 2016) and on using these calculations to infer the effect of crystal shapes on snow optical properties. Several studies have already shown that the effect of shape is more pronounced on bidirectional reflectance (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, many studies have focused on retrieving the single-scattering properties of individual ice crystals with "idealized" shapes (e.g. Xie et al, 2006;Picard et al, 2009;Liou et al, 2011;Räisänen et al, 2015;Dang et al, 2016) and on using these calculations to infer the effect of crystal shapes on snow optical properties. Several studies have already shown that the effect of shape is more pronounced on bidirectional reflectance (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and modelling the variations in snow directional reflectance with snow microstructure are essential to correctly interpret satellite data (Schaepman-Strub et al, 2006). Moreover, the sensitivity of snow directional reflectance to crystal shapes at least for high absorptive wavelengths (Xie et al, 2006;Dumont et al, 2010;Krol and Löwe, 2016a) makes snow directional reflectance a good candidate to provide an objective measurement of snow morphology. This characterization is often performed using the grain types defined in Fierz et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Still, in situ studies of snow mostly consist of following time lapse metamorphism for different types of snow [16] and with controlled thermal gradients or other particular conditions [17,18]. The ultimate goal is usually to compute snow effective properties [19] or model snow behavior [20,21,22]. Moreover, curvature change is a key feature of snow metamorphism and its investigation reveals underlying processes at work [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The CLD p (i) (l) of phase i denotes the probability p (i) (l)dl of finding a random chord of length between l and l + dl in phase i (Torquato, 2002), thus 5 giving us information on the thicknesses of the elements constituting the considered phase. In the case of snow, which is known to be an anisotropic material with an orthotropic axis corresponding to the vertical (z) direction (see Calonne et al, 2011Calonne et al, , 2012Löwe et al, 2013;Calonne et al, 2014b, a;Wautier et al, 2015;Srivastava et al, 2016;Wautier et al, 2017), the CLD measured along a particular line depends on its direction. Assuming that the anisotropy is small, we consider the statistical characteristics of a sample in the three Cartesian directions.…”
Section: Chord Length Distributionmentioning
confidence: 99%